1990
DOI: 10.1021/ac00221a013
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic separations of proteins in capillaries with hydrolytically-stable surface structures

Abstract: A procedure for obtaining highly stable coated capillaries for use in capillary electrophoresis (CE) is described. Reaction of surface-chlorinated fused silica capillaries with the Grignard reagent, vinyl magnesium bromide, followed by reaction of the vinyl group with acrylamide, results in an immobilized layer of polyacrylamide attached through hydrolytically stable Si-C bonds. This method is an extension of the capillary coating procedure described previously by Hjerten, differing in the means by which the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
124
0
1

Year Published

1992
1992
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 337 publications
(129 citation statements)
references
References 27 publications
(24 reference statements)
4
124
0
1
Order By: Relevance
“…The use of polymeric coatings has led to high efficiency and reproducible protein separations preventing the surface adsorptions. Polymers ranging from highly hydrophobic to highly hydrophilic were used for this purpose to obtain efficient separations of proteins in CE [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The use of polymeric coatings has led to high efficiency and reproducible protein separations preventing the surface adsorptions. Polymers ranging from highly hydrophobic to highly hydrophilic were used for this purpose to obtain efficient separations of proteins in CE [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Also, silanization by trimethylchlorosilane (TMCS) was used to silylate the column surface and reduce the EOF [13,21]. Again, polymer and a number of other coatings were applied by different authors [22][23][24][25][26][27][28] and a decreased EOF was generally observed. Terabe et al [29] investigated the effects on the EOF of hydrophobic and hydrophillic coatings.…”
Section: Introductionmentioning
confidence: 99%
“…There are several chemistries applied to polymer attachment on the wall: silane bifunctional reagent [71], Grignard chemistry [72], thermal immobilization [73], and vapor deposition.…”
Section: Static Wall Coatingmentioning
confidence: 99%